Sleep disorders and post-COVID-19 syndrome: a narrative review - Arredondo Nontol, Rodolfo (2024)
The COVID-19 pandemic has resulted in both high mortality rates and a decrease in the response of health services worldwide. Many people changed their lifestyles due to the deterioration of their health both during the acute and post-illness stages. Depression, and especially sleep disorders, deserve attention due to their high prevalence within the so-called post-COVID-19 syndrome because they are associated with a deterioration in the quality of life of those affected. Knowing its prevalence and understanding its pathophysiology, clinical spectrum and treatment methods remain matters of research. The objective of this narrative review is to present the latest findings on sleep disorders as manifestations of post-COVID-19 syndrome. For this purpose, scientific literature was consulted using three databases—PubMed, Scopus and SciELO—resulting in a total of 867 articles, which were reviewed by title and abstract. This search was updated twice, resulting in 61 articles, which were included in this narrative review. A prevalence of sleep disorders in post-COVID-19 syndrome ranging from 9.7 % to 50 % is noted; its cause is identified as multifactorial, and the systemic inflammatory response may play a fundamental role due to the toxic action of cytokines and the poor neuronal response to revert the inflammatory process. Insomnia is the most frequent symptom; being female and suffering from concomitant depressive disorders are prevalent risk factors. There is a possible beneficial effect on symptom control resulting from antidepressants as well as non-pharmacological treatments such as individualized physical therapy and an antioxidant nutritional regimen. It is concluded that many gaps remain in the understanding of this pathology and further research is needed to elucidate them.